Studies on ethanol production using immobilized cells of Kluyveromyces thermotolerans in a packed bed reactor - Singh N.L.; Srivastava P.; Mishra P.K. (My University, 2025)
Optimization of a suitable process for whole cell immobilization of Kluyveromyces thermtolerans in calcium alginate, coconut coir, bagasse, and jute stick for ethanol production in a packed bed bioreactor is presented. Specific ethanol production of immobilized cells for jute stick was maximum. Cell to carrier ratio (9: 10) was optimum.